Draft Genome Sequence of the Lytic Salmonella Phage OSY-STA, Which Infects Multiple Salmonella Serovars - Yi, Yue (Microbiol Resour Announc, 2020)
Bacteriophage OSY-STA is a new anti-Salmonella phage that was isolated from a chicken farm in Ohio. It is a promising candidate for food safety applications, considering its efficiency in infecting several Salmonella enterica serovars. The current work presents its genomic characteristics. Salmonella phage OSY-STA has a 111,039-bp genome and 166 open reading frames.